2016
DOI: 10.1038/sc.2016.87
|View full text |Cite
|
Sign up to set email alerts
|

rTMS of the prefrontal cortex has analgesic effects on neuropathic pain in subjects with spinal cord injury

Abstract: The findings of this preliminary study in a small patient sample suggest that rTMS of the PMC/DLPFC may be effective in relieving neuropathic pain in SCI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 54 publications
2
77
0
3
Order By: Relevance
“…ACC is linked to the affective processing of pain, and also likely serves as an important relay station in descending inhibitory control of pain (Bingel et al, 2006; Lieberman and Eisenberger, 2015; Qu et al, 2011; Rainville et al, 1997; Rance et al, 2014; Russo and Sheth, 2015). PF has been proposed as a modulatory area for pain (Hardy and Haigler, 1985; Jahn et al, 2016; Lorenz et al, 2003; Nardone et al, 2017; Wiech et al, 2006). Nevertheless, detection of nociceptive heat-evoked fMRI signal changes in these two cortices (ACC and PF), as well as their robust functional connections to the pIns region under anesthesia, further supports their fundamental roles in nociceptive information processing without consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…ACC is linked to the affective processing of pain, and also likely serves as an important relay station in descending inhibitory control of pain (Bingel et al, 2006; Lieberman and Eisenberger, 2015; Qu et al, 2011; Rainville et al, 1997; Rance et al, 2014; Russo and Sheth, 2015). PF has been proposed as a modulatory area for pain (Hardy and Haigler, 1985; Jahn et al, 2016; Lorenz et al, 2003; Nardone et al, 2017; Wiech et al, 2006). Nevertheless, detection of nociceptive heat-evoked fMRI signal changes in these two cortices (ACC and PF), as well as their robust functional connections to the pIns region under anesthesia, further supports their fundamental roles in nociceptive information processing without consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Three RCTs (44,47,48) and two prospective observational studies (45,46) revealed that rTMS effectively managed chronic central pain in patients with SCI. Among the RCTs, Nardone et al (48) performed 10 sessions of 10-Hz rTMS stimulation over the left prefrontal cortex in 12 patients with complete or incomplete motor SCI. The VAS scores of six patients in the real rTMS group decreased over time, and the differences in VAS scores between patients in the real rTMS group and the six patients in the sham group showed that rTMS effectively relieved pain in patients with SCI after 2 weeks of treatment.…”
Section: Central Pain After Scimentioning
confidence: 99%
“…In addition, the responsiveness of varies types of neuropathic pain was not further differentiated [24][25][26][27]. Stimulation of DLPFC is based on the concept that, besides chronic pain, a positive effect is exerted on the depression component (e.g., [15,28]).…”
Section: Application Of Rtms and Tdcs In Pain Patientsmentioning
confidence: 99%